Pendekatan Burhani sebagai Fondasi Rasional dalam Analisis Wacana Ilmiah Islam - Nugraha, Aszahra Regita; Faradisa, Amirah; Maulidyah, Shandy; Hastin, Nisrina Nurlaela Yumna; Auliza, Viranda Rizky; Aulia, Izza Asti; Kurniawan, Taufiq (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Islam has a comprehensive epistemology as the primary foundation for acquiring knowledge. In general, epistemology in Islam exhibits three strong tendencies: bayani, irfani, and burhani. These three forms of reasoning originate from the thoughts of Muhammad Abid al-Jabiri, a contemporary Moroccan philosopher known for his efforts to develop a philosophy that combines rationality, authority, and intuition. According to al-Jabiri, these three forms of reasoning serve not only as tools for acquiring knowledge but also as a way to understand the relationship between humans and God, nature, and themselves. Bayani epistemology emphasizes the study of texts (nas), ijma, and ijtihad as basic references for justifying certain beliefs. This study summarizes the concept that burhani epistemology emphasizes the innate human potential in terms of intuition, senses, experimentation, and conceptualization, expressed as